Formalized classification of European fen vegetation at the alliance level. Issue 1 (2nd November 2016) - Peterka, Tomáš; Hájek, Michal; Jiroušek, Martin; Jiménez‐Alfaro, Borja; Aunina, Liene; Bergamini, Ariel; Dítě, Daniel; Felbaba‐Klushyna, Ljuba; Graf, Ulrich; Hájková, Petra; Hettenbergerová, Eva; Ivchenko, Tatiana G.; et al.
Abstract: Aims: Phytosociological classification of fen vegetation ( Scheuchzerio palustris‐Caricetea fuscae class) differs among European countries. Here we propose a unified vegetation classification of European fens at the alliance level, provide unequivocal assignment rules for individual vegetation plots, identify diagnostic species of fen alliances, and map their distribution. Location: Europe, western Siberia and SE Greenland. Methods: 29 049 vegetation‐plot records of fens were selected from databases using a list of specialist fen species. Formal definitions of alliances were created using the presence, absence and abundance of Cocktail‐based species groups and indicator species. DCA visualized the similarities among the alliances in an ordination space. The ISOPAM classification algorithm was applied to regional subsets with homogeneous plot size to check whether the classification based on formal definitions matches the results of unsupervised classifications. Results: The following alliances were defined: Caricion viridulo‐trinervis (sub‐halophytic Atlantic dune‐slack fens), Caricion davallianae (temperate calcareous fens), Caricion atrofusco‐saxatilis (arcto‐alpine calcareous fens), Stygio‐Caricion limosae (boreal topogenic brown‐moss fens), Sphagno warnstorfii‐Tomentypnion nitentis ( Sphagnum‐ brown‐moss rich fens), Saxifrago‐Tomentypnion (continental to boreo‐continental nitrogen‐limited brown‐moss rich fens), Narthecion scardici (alpine fens with Balkan endemics), Caricion stantis (arctic brown‐moss rich fens), Anagallido tenellae‐Juncion bulbosi (Ibero‐Atlantic moderately rich fens), Drepanocladion exannulati (arcto‐boreal‐alpine non‐calcareous fens), Caricion fuscae (temperate moderately rich fens), Sphagno‐Caricion canescentis (poor fens) and Scheuchzerion palustris (dystrophic hollows). The main variation in the species composition of European fens reflected site chemistry (pH, mineral richness) and sorted the plots from calcareous and extremely rich fens, through rich and moderately rich fens, to poor fens and dystrophic hollows. ISOPAM classified regional subsets according to this gradient, supporting the ecological meaningfulness of this classification concept on both the regional and continental scale. Geographic/macroclimatic variation was reflected in the second most important gradient. Conclusions: The pan‐European classification of fen vegetation was proposed and supported by the data for the first time. Formal definitions developed here allow consistent and unequivocal assignment of individual vegetation plots to fen alliances at the continental scale. Abstract : The pan‐European classification of fen vegetation ( Scheuchzerio palustris‐Caricetea fuscae class) is proposed and supported by the data for the first time. Formal definitions developed here allow consistent and unequivocal assignment of individual vegetation plots to fen alliances at the continental scale.